(untitled) (World Economics and Finance Bulletin, 2022)
The major objective of this study is to examine the contribution of female education to poverty reduction in Nigeria. It posits on the correction of educational imbalance that existed between the females and their male counterparts in Nigeria during the turn of the 20th century. Analytical survey design was used to enumerate the various advantages and contributions of female education to poverty reduction in Nigeria. According to 2010 National census, more than 58percent of Nigeria’s population are females. Denying the female folk their rightful place Nigeria’s economic development does not only result in prejudice but economic sabotage. Females in Nigeria have the ability to engage in well-paid jobs, contribute to household economic welfare, maintain the health functions of the family, thereby contributing meaningfully to the country’s Gross Domestic Product. The study therefore recommends that: females should be given equal opportunity with their male counterparts in educational pursuits; there should be legislation against forced and early marriages in the country; the illiterate idea of subjecting the female to slavery status should be abolish and women fertility rates especially in the rural settings should be reduced through formal education